Socio-econ-environmental impacts of rural ecotourism development in Tun Sakaran Marine Park, Sabah, Malaysia - Chia, Kei Wei; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (2012)
Malaysia is located in the Coral Triangle of the South China Sea, with extraordinary reef coverage of approximately 3,600 km²; it is rich in marine biodiversity. The gazzettement of the Marine Park and establishing the park as a rural ecotourism site are aimed at protecting the fragile marine resources from the impacts of human activities. Tourism activities in Marine parks, if not properly managed, may destroy the natural resources which it depends on, and thus diminish the quality of experience. At the same time, local communities may depend on the very same resources for their livelihood. These human activities may affect the sustainability of tourism in the future. Thus, a sustainable tourism development requires a balanced environmental management and the balance should be measured before the critical level is reached. The main objective of this paper is to explore some of the significant issues faced by the management of Marine Parks in Malaysia, particularly to the Tun Sakaran Marine Park based on socio-cultural, economics, and environmental perspectives and to propose some recommendations to the management of Marine Park.